(3eTcGI GdUhGH aj TQM NdGUI GdMSGHs - (3GdHGQi GHf eMeO HGbQ GdehShi GdSjO Ydj GdNhfSGQis; (3HgGA GdOjf eMeO Hf MSjf GdMGQKj GdgeOGfj GdTjYj GdYGedj,J (B1031 (3g` s
(3ChdgG (B:s
(3CeG HYO ajbhd GdeaJbQ Edi QMeI Gddg GdHGQi GHf eMeO GdNhGfSGQi gPg JYdjbGJ YRjRI hJhVjMGJ hLjRg YdbJgG GdJeGS Ydi GdQSGdI GdeSeGg HNdGUI GdMSGH s
(3BNQgG (B:s
(3aEf cKjQkG ef eWGdHgG hhGaQkG ef ebGUOgG hGMQi HGdUjGfg hGdcJeGf hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3GfXQ GdNdGUI GdMSGH L(B1 (3U` (B720s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdQjGVjGJs